![\huge \boxed{\mathfrak{Question} \downarrow}](https://tex.z-dn.net/?f=%20%5Chuge%20%5Cboxed%7B%5Cmathfrak%7BQuestion%7D%20%5Cdownarrow%7D)
Factor each of the following differences of two squares and write your answer together with solution.
![\large \boxed{\mathbb{ANSWER\: WITH\: EXPLANATION} \downarrow}](https://tex.z-dn.net/?f=%20%5Clarge%20%5Cboxed%7B%5Cmathbb%7BANSWER%5C%3A%20WITH%5C%3A%20EXPLANATION%7D%20%5Cdownarrow%7D)
<h3><u>1. x² - 36</u></h3>
![\sf \: x ^ { 2 } - 36](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%20x%20%5E%20%7B%202%20%7D%20-%2036)
Rewrite
. The difference of squares can be factored using the rule:
.
![\boxed{ \boxed{ \bf\left(x-6\right)\left(x+6\right) }}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Cboxed%7B%20%5Cbf%5Cleft%28x-6%5Cright%29%5Cleft%28x%2B6%5Cright%29%20%7D%7D)
__________________
<h3><u>2. 49 - x²</u></h3>
![\sf \: 49 - x ^ { 2 }](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%2049%20-%20x%20%5E%20%7B%202%20%7D)
Rewrite 49-x² as 7²-x². The difference of squares can be factored using the rule:
.
![\sf \: \left(7-x\right)\left(7+x\right)](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%20%5Cleft%287-x%5Cright%29%5Cleft%287%2Bx%5Cright%29%20)
Reorder the terms.
![\boxed{ \boxed{ \bf\left(-x+7\right)\left(x+7\right) }}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Cboxed%7B%20%5Cbf%5Cleft%28-x%2B7%5Cright%29%5Cleft%28x%2B7%5Cright%29%20%7D%7D)
__________________
<h3><u>3. 81 - c²</u></h3>
![\sf \: 81 - c ^ { 2 }](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%2081%20-%20c%20%5E%20%7B%202%20%7D)
Rewrite 81-c²as 9²-c². The difference of squares can be factored using the rule:
.
![\sf\left(9-c\right)\left(9+c\right)](https://tex.z-dn.net/?f=%20%5Csf%5Cleft%289-c%5Cright%29%5Cleft%289%2Bc%5Cright%29%20)
Reorder the terms.
![\boxed{ \boxed{ \bf\left(-c+9\right)\left(c+9\right) }}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Cboxed%7B%20%5Cbf%5Cleft%28-c%2B9%5Cright%29%5Cleft%28c%2B9%5Cright%29%20%7D%7D)
__________________
<h3><u>4</u><u>.</u><u> </u><u>m²</u><u>n</u><u>²</u><u> </u><u>-</u><u> </u><u>1</u></h3>
![\sf \: m ^ { 2 } n ^ { 2 } - 1](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%20m%20%5E%20%7B%202%20%7D%20n%20%5E%20%7B%202%20%7D%20-%201)
Rewrite m²n² - 1 as
. The difference of squares can be factored using the rule:
.
![\boxed{ \boxed{ \bf\left(mn-1\right)\left(mn+1\right) }}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Cboxed%7B%20%5Cbf%5Cleft%28mn-1%5Cright%29%5Cleft%28mn%2B1%5Cright%29%20%7D%7D)
Answer:
Get a calculator a graphing calculator and insert each one of those in it
Answer is
= 1.24*5+1.1*2.20+4.5*0.68
= <u>11.68</u>
8x + 6 - 2x = 34x
Simplify 8x +6 - 2x to 6x + 6:
6x + 6 = 34x
Subtract 6x from both sides:
6 = 34x- 6x
Simplify 34x - 6x to 28x:
6 = 28x
Divide both sides by 28:
![\frac{6}{28}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B28%7D%20)
= x
Simplify
![\frac{6}{28}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B28%7D%20)
to
![\frac{3}{14}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B14%7D%20)
:
![\frac{3}{14}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B14%7D%20)
= x
Now switch sides and the answer is:
x =
![\frac{3}{14}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B14%7D%20)
:) <3